2020
DOI: 10.1530/ec-20-0374
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the prognostic molecular markers in medullary thyroid carcinoma

Abstract: Medullary thyroid cancer (MTC) is a rare thyroid malignancy, which arises from parafollicular C-cells. It occurs in the hereditary or sporadic form. Hereditary type is a consequence of activation of the RET proto-oncogene by germline mutations, whereas about 80% of sporadic MTC tumors harbor somatic, mainly RET or rarely RAS mutations. According to the current ATA guidelines, a postoperative MTC risk stratification and long-term follow-up are mainly based on histopathological data, including tumor stage, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 79 publications
(90 reference statements)
0
14
0
1
Order By: Relevance
“…In case of widespread regional or metastatic disease, surgical interventions are not associated with a higher cure rate, therefore, less aggressive local treatment procedures should be preferred. Systemic therapy is employed in multi-metastatic and rapidly progressing malignancies [ 61 , 104 , 105 ].…”
Section: Current Diagnostic and Treatment Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of widespread regional or metastatic disease, surgical interventions are not associated with a higher cure rate, therefore, less aggressive local treatment procedures should be preferred. Systemic therapy is employed in multi-metastatic and rapidly progressing malignancies [ 61 , 104 , 105 ].…”
Section: Current Diagnostic and Treatment Strategiesmentioning
confidence: 99%
“…As already mentioned, current guidelines on management of MTC patients recommend cabozantinib and vandetanib as the first-line single-agent systemic therapy in patients with advanced progressive MTC, based on their documented ability to improve PFS ( Table 1 ). Both drugs inhibit RET kinase activity to some extent, however, their major anticancer effect is due to their strong inhibition of angiogenesis [ 13 , 61 , 105 , 155 ]. The list of on-going clinical trials for treatment of MTC is provided in Table 4 .…”
Section: Currently Used and Investigated Targeted Therapies In Tcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognosis of radiotherapy in medullary thyroid carcinoma patients without distant metastasis MTC currently has a poor prognosis and few clinical treatments, and it presents more advanced disease symptoms and a worse prognosis than well-differentiated thyroid carcinoma (5). On presentation, half of patients have local lesions, while 35% of patients extend to surrounding tissues and 13% of patients have distant metastases (6).…”
Section: Original Articlementioning
confidence: 99%
“…Single-cell transcriptomes provided new insights into cell-cell interactions in multiple types of cancer (Zhang et al, 2019;Davis et al, 2020;Wieland et al, 2020). Some molecular studies reported the advances in follicular thyroid carcinoma and medullary thyroid carcinoma (Ceolin et al, 2012;Mohammadi and Hedayati, 2017;Borowczyk et al, 2019;Oczko-Wojciechowska et al, 2020). A recent scRNA-seq study made a comparison of tumor microenvironment (TME) in PTC between genders (Peng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%